2018
DOI: 10.4317/medoral.22493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ondansetron versus Clonidine efficacy for prevention of postoperative pain, nausea and vomiting after orthognathic surgeries: A triple blind randomized controlled trial

Abstract: BackgroundThe aim of this randomized controlled triple blind trial was to compare the efficacy of clonidine with dexamethasone versus ondansetron with dexamethasone for postoperative pain, nausea and vomiting prevention in orthognathic surgery patients.Material and MethodsIn this clinical trial study, 30 consecutive patients with skeletal class III deformities were candidates for orthognathic surgery in Qaem hospital, Mashhad University of medical sciences, Mashhad, Iran from March to November 2017. These subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 27 publications
3
26
0
2
Order By: Relevance
“…A 5-hydroxytryptamine 3 receptor antagonist plus dexamethasone is a recommended combination for PONV prophylaxis. However, even with combined therapy, the incidence of postoperative nausea was up to 50% in orthognathic patients and higher in bimaxillary cases [ 9 ]. Therefore, combined therapy with a third drug of another category is reasonable for preventing PONV in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…A 5-hydroxytryptamine 3 receptor antagonist plus dexamethasone is a recommended combination for PONV prophylaxis. However, even with combined therapy, the incidence of postoperative nausea was up to 50% in orthognathic patients and higher in bimaxillary cases [ 9 ]. Therefore, combined therapy with a third drug of another category is reasonable for preventing PONV in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Orthognathic surgery is a widely performed surgical procedure with increasing popularity over the past few decades [1][2][3][4][5] . The state of the art is used to correct severe jaw deformities and maintain a stable dentoskeletal relationship [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Orthognathic surgery is a widely performed surgical procedure with increasing popularity over the past few decades [1][2][3][4][5] . The state of the art is used to correct severe jaw deformities and maintain a stable dentoskeletal relationship [1][2][3][4][5][6] . Adequate and efficient acute pain control after surgery is a crucial component for inpatient care and renders uncomplicated recovery and hospital discharge 1,2,7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin (5-hydroxytryptamine 3 [5-HT3]) receptor antagonists, such as ondansetron, granisetron, and dolasetron, are frequently used for PONV prophylaxis. 4 , 5 These antagonists have a considerably short duration of action and are thus commonly used in the immediate postoperative period, but they are less effective at preventing postoperative vomiting (POV) than postoperative nausea (PON). 6 Several meta-analyses have reported that an intravenous dose of the serotonin antagonist ramosetron (0.3 mg) has better efficacy and longer duration of action than other serotonin receptor antagonists after nonorthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%